BOSHLANG‘ICH SINFLARDA ONA TILI FANINI CHUQUR O‘ZLASHTIRILISHGA QO‘YILGAN ZAMONAVIY TALABLAR - Babasheva, G.B. (SCIENCE and SOCIETY, 2024)
This article tells about what to pay attention to and what methods to use to master the subject of native language in elementary grades.
Keywords: reading technique; expression of opinion in written form; independent thinking; having one’s own opinion